DECREASED ATHLETE MOTOR SKILLS: BEFORE AND AFTER ACTIVITY CORONAVIRUS DISEASE (COVID-19) PANDEMIC. - Pardilla, Herli; Henjilito, Raffly; Asilestari, Putri; Husnayadi, Iqbal (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2020)
The purpose of the study. is study was to look at the impact of pandemic 19 before and after Activity Coronavirus disease (B-A COVID-19P) on the performance of athletes' motor skills (MS) Materials and methods. The participants (Sample / N = 40) are national athletes in the Field Jumping category (Triple jump, Long jump and High jump), Riau Province of Indonesia, aged 18–20 years. The test instrument in determining the level of MS in athletes is the Motor Ability Test (7 item test) Results. The results of the Paired Sample test B-A COVID-19P have sig values. ie 0.00 If seen with a significance standard of 0.05 or 5%, p-values of 0.000 <0.05 and H1 are accepted. This means that there are significant differences between motor skills in B-A COVID-19P. Conclusions. With the conclusion that MS in track and field athletes there is a decrease in performance after the impact of the Covid-19 pandemic.